IMPLEMENTASI NILAI PANCASILA DALAM AJARAN ORGANISASI PENCAK SILAT DI UKM PERSAUDARAAN SETIA HATI TERATER UNIVERSITAS NEGERI SURABAYA - DIPONEGORO, SULTHONI EDGAR; Agus Satmoko Adi (Kajian Moral dan Kewarganegaraan, 2024)
The Pencak Silat organization Persaudaraan Setia Hati Terate (PSHT) plays an important role in teaching Pancasila values, especially through the PSHT Student Activity Unit (UKM) at Surabaya State University (UNESA). This study aims to analyze the implementation of Pancasila values in the teachings of PSHT to shape student character based on moral, spiritual, and nationality. This research uses descriptive qualitative method, this research collects data through interviews with UKM members, observation of activities, and document analysis. The data were analyzed thematically to identify the form of implementation, constraints, and impacts. The results showed that Pancasila values are applied in various aspects of UNESA PSHT UKM activities, despite facing obstacles such as diverse member understanding and the challenge of maintaining consistency of application in the midst of organizational activities. The implementation of Pancasila values in PSHT SMEs has a positive impact in shaping the character of Pancasila, strengthening solidarity, and increasing the sense of nationality. This study concludes that the teachings of PSHT can be a strategic forum for instilling Pancasila values in students. Strengthening a more structured program is needed so that the implementation of these values remains sustainable and effective.